Comparative Analysis of The Performance of The Composite Stock Price Index (IHSG) With the Indonesian Sharia Stock Index (ISSI) During The Covid-19 Pandemic - Mikrad Mikrad; Agung Budi; Hendra Galuh Febrianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The objective of this study is to determine whether there is a difference in performance between the conventional stock index and the Islamic stock index. If the performance is different, what is the magnitude of the difference. This research is important to be done to be used as a reference and also a preference for the community to determine which investment instrument is the right one and will be profitable for them. This type of research is comparative. The method used in this study is a quantitative method with secondary data. Secondary data will be accessed through the official website. Secondary data is then processed so that it can provide the right conclusions. The results of this study indicate that there is no significant difference between the conventional stock index and the Islamic stock index in terms of Sharpe's performance. However, there is a significant difference between the conventional stock index and the Islamic stock index in terms of Treynor and Jensen's performance.